Evaluasi Pelaksanaan Kebijakan Penertiban PKL sesuai Peraturan Daerah Nomor 11 Tahun 2005 di Kota Padang - Prawinda, Cindy; Adnan, M. Fachri (Al-DYAS, 2025)
This study evaluates the implementation of the street vendor (PKL) regulation policy in Padang City based on Regional Regulation No. 11 of 2005. The main focus is to assess the effectiveness of the policy and identify the factors that influence it. A descriptive qualitative approach was used, with data collected through interviews and field document analysis. The results indicate that the policy implementation has not been fully effective. Communication between related agencies and street vendors is still conducted informally and lacks comprehensive outreach, resulting in inconsistent and unclear information dissemination. The resources used for enforcement, particularly from the Civil Service Police Unit (Satpol PP), are highly dependent on requests from the Department of Trade, leading to irregular implementation. The disposition or attitude of the enforcement personnel also affects policy outcomes in the field. Furthermore, the bureaucratic structure, which involves multiple agencies, creates coordination complexity that impacts the effectiveness of the enforcement. The conclusion of this study is that improvements are needed in communication, inter-agency coordination, and the implementation structure to ensure that the regulation of street vendors in Padang City becomes more effective and sustainable.